Present to a life dedicated to books: Gift to İsmail E. Erünsal - Özhan Sağlık (Türk Kütüphaneciliği)
When thinking about the scholars produced significant studies on book, library and culture history Prof. Dr. İsmail Erünsal is one of the precious first-minded personage. It has known that İsmail Erünsal has dedicated his life to wisdow and science. In the face of this dedication, students, friends and scholar fellows of İsmail Erünsal had an idea about gift book as a respect and gratitude. This idea has realized in 2014 and forty four articled gift book about history, literature, sufism, librarianship and archives has been published. Even this gift book has been reviewed in general terms in othe circles, it has not been seen the arcticles contained have been reviewed enough. In this study, due to being in the scope of our profession articles about librarianship and archives contained in the gift book have been strived to be reviewed.